Millimeter-Wave Receiver Concepts for 77 GHz Automotive Radar in Silicon-Germanium Technology - Kissinger, Dietmar; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
The book presents the analysis and design of integrated automotive radar receivers in Silicon-Germanium technology, for use in complex multi-channel radar transceiver front-ends in the 77GHz frequency band. The main emphasis of the work is the realization of high-linearity and low-power modular receiver channels as well as the investigation of millimeter-wave integrated test concepts for the receiver front-end.
Introduction -- Radar Fundamentals -- Silicon-Germanium Bipolar Technology -- Millimeter-Wave Receiver Concepts -- Differential 77-GHz High-Linearity Receiver Front-End -- Differential 77-GHz Current Re-Use Low-Noise Amplifier -- Millimeter-Wave Built-In Test Concepts -- Direct-Conversion Receiver Built-In Test Architecture -- Recursive 77-GHz Mixer Test Architecture -- Conclusion.
Keywords: Engineering; Electronics; Systems engineering; Engineering; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Automotive Engineering